High prevalence of early repolarization in the paediatric relatives of sudden arrhythmic death syndrome victims and in normal controls. Issue 8 (13th December 2016) - McCorquodale, Anna; Poulton, Rachel; Hendry, Jennifer; Norrish, Gabrielle; Field, Ella; Mead-Regan, Sarah; Lowe, Martin; Kaski, Juan Pablo
Abstract: Aims: Elevation of the ECG J-point in the inferior and lateral leads (early repolarization) has been described in survivors of ventricular fibrillation (VF) arrest and occurs in adult first-degree relatives of sudden cardiac death (SCD) probands at a frequency significantly greater than in controls, raising the possibility that this could represent an independent risk factor in the aetiology of SCD. However, data on early repolarization in the paediatric population are lacking. This study aimed to assess the prevalence of early repolarization in paediatric first-degree relatives of sudden arrhythmic death syndrome (SADS) victims. Methods and results: Paediatric relatives (aged <18 years) of SADS probands referred to the Inherited Arrhythmia Clinic at Great Ormond Street Hospital had their initial screening ECG reviewed for evidence of J-point elevation. J-point elevation was defined as QRS-ST slurring or a discrete notch in two or more inferior (II, III, aVF) or lateral (I, aVL, V4, V5, V6) leads with the change beginning >1 mV from baseline. The ECGs of 77 consecutive paediatric first-degree relatives of SADS victims from 46 families were reviewed by two assessors. J-point elevation was present in 24 patients (31%) of this patient group compared with the reported prevalence of 5–13% in the published general paediatric population ( P = 0.02) and that of 19% in the internal control group ( P = 0.07). Subgroup analysis according to J-point elevation and ST segment morphologies showed a significantly higher prevalence of inferior early repolarization 0.1–0.2 mV in the study group compared with controls (75 vs. 38%; P = 0.02). Conclusion: Inferolateral J-point elevation occurs in a substantial proportion of paediatric first-degree relatives of SADS probands with a similar prevalence to that described in adults. This suggests that early repolarization could be an important inherited trait when evaluating relatives of SADS victims. However, prospective follow-up of this group of children is important to establish the implication of this finding in future risk stratification, given the apparently high prevalence in normal individuals.